2022
DOI: 10.22373/share.v11i1.10726
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Effect of Covid-19 on the Performance of the Sharia Stock Index?

Abstract: The implementation of social distance during the Covid-19 pandemic has an impact on economic activity and stock market indices. Evidently, the increase in confirmed cases has had no discernible effect on economic activity. This article compares the performance and returns of the Islamic stock index before and after the pandemic. Data were gathered from the Jakarta Islamic Index (JII), the Indonesian Sharia Stock Index (ISSI), and the Jakarta Islamic Index 70 (JII70) for the April 2019-March 2020 (pre-Covid-19)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…The same thing was stated by Huda et al, (2022), their study's findings clearly demonstrate that performance during COVID-19 was better to that of prior COVID-19. This is evident in the computation of return and risk for Islamic stock indexes.…”
Section: Cluster 3: Covid-19 Effect On Indonesia Sharia Stock Indexsupporting
confidence: 77%
“…The same thing was stated by Huda et al, (2022), their study's findings clearly demonstrate that performance during COVID-19 was better to that of prior COVID-19. This is evident in the computation of return and risk for Islamic stock indexes.…”
Section: Cluster 3: Covid-19 Effect On Indonesia Sharia Stock Indexsupporting
confidence: 77%
“…Furthermore, Novrizal et al (2022) conducted a study on firms listed on the Jakarta Islamic Index and found a positive relationship between profitability and firm value. Notably, during the COVID-19 pandemic, the performance of the sharia stock index increased, as reported by Huda et al (2022).…”
mentioning
confidence: 88%
“…According to a study by (Mirzaei, Saad, and Emrouznejad, 2022) Also, a study by (Huda, Rini, Setianingrum, and Zulihar, 2022) demonstrates that social exclusion during the COVID-19 pandemic is imposed using stock market and economic indicators. The rise in confirmed cases has not significantly impacted the business, evaluating the outcomes and achievement of Islamic stock indices before and after the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%